Desain Konstruksi Press Tool Sebagai Alat Bending Bentuk V Dengan Garis Bending Max. 300mm - Muhammad Arsyad Suyuti; Muhammad Iswar; Rusdi Nur; Erniyanti Erniyanti (Politeknik Negeri Ujung Pandang, 2019)
Nowadays, the process of metal forming in the machining industry and welding workshop is developing very rapidly especially in the plate bending process. The bending process is the formation of metals which generally use plates or rods of both ferrous and non-ferrous metal materials by bending, which in the bending process will cause stretching or stretching on the neutral plane axis along the bending area and produce a straight bend line. The use of appropriate technology machines has been widely used to increase productivity, efficiency, and effectiveness in the production process for community businesses, especially those in the regions. One of the appropriate technologies that might be applied in the bending process is a hydraulic jack press that is equipped with a press tool. Press tool is one type of product forming, cutting and bending tools from the basic material of sheet plates whose operations are using a press tool. The results of the design of press tool bending tool V have a length of 300 mm bending line, 33 mm bending width, 110 mm spring height, free step distance of 19 mm. The punch angle used is 85⁰ with the punch radius used is 1.5 mm while the die angle is 85⁰. The selected punch and die material is Steel AISI 1045 HV HR.